Weaning at Anglo‐Saxon raunds: Implications for changing breastfeeding practice in britain over two millennia. Issue 4 (18th July 2013) - Haydock, Hannah; Clarke, Leon; Craig‐Atkins, Elizabeth; Howcroft, Rachel; Buckberry, Jo
ABSTRACT This study investigated stable‐isotope ratio evidence of weaning for the late Anglo‐Saxon population of Raunds Furnells, Northamptonshire, UK. δ15N and δ13C values in rib collagen were obtained for individuals of different ages to assess the weaning age of infants within the population. A peak in δ15N values at about 2‐year‐old, followed by a decline in δ15N values until age three, indicates a change in diet at that age. This change in nitrogen isotope ratios corresponds with the mortality profile from the site, as well as with archaeological and documentary evidence on attitudes towards juveniles in the Anglo‐Saxon period. The pattern of δ13C values was less clear. Comparison of the predicted age of weaning to published data from sites dating from the Iron Age to the 19th century in Britain reveals a pattern of changing weaning practices over time, with increasingly earlier commencement and shorter periods of complementary feeding in more recent periods. Such a change has implications for the interpretation of socioeconomic changes during this period of British history, since earlier weaning is associated with decreased birth spacing, and could thus have contributed to population growth. Am J Phys Anthropol 151:604–612, 2013. © 2013 Wiley Periodicals, Inc.